Selective Disruption of the Blood–Brain Barrier by Zika Virus - Leda, Ana Rachel; Bertrand, Luc; Andras, Ibolya Edit; El-Hage, Nazira; Nair, Madhavan; Toborek, Michal (Frontiers in Microbiology, 2019)
The blood-brain barrier (BBB) selectively regulates the cellular exchange of macromolecules between the circulation and the central nervous system (CNS). Here, we hypothesize that Zika virus (ZIKV) infects the brain via disrupted BBB and altered expression of tight junction (TJ) proteins, which are structural components of the BBB. To assess this hypothesis, in vitro and in vivo studies were performed using three different strains of ZIKV: Honduras (ZIKV-H), Puerto Rico (ZIKV-PR), and Uganda (ZIKV-U). Primary human brain microvascular endothelial cells (BMECs) were productively infected by all studied ZIKV strains at MOI 0.01 as analyzed by a plaque assay, immunofluorescence for NS1 protein, and qRT-PCR at 2 and 6 days post-infection (dpi). Compared to mock-infected controls, expression level of ZO-1 was significantly upregulated in ZIKV-H-infected BMECs, while occludin and claudin-5 levels were significantly downregulated in BMECs infected by all three studied viral strains. Interestingly, BMEC permeability was not disturbed by ZIKV infection, even in the presence of a very high viral load (MOI 10). All studied ZIKV strains productively infected wild-type C57BL/J mice after intravenous infection with 107 PFU. Viral load was detected in the plasma, spleen, and brain from 1 to 8 dpi. Peak brain infection was observed at 2dpi; therefore, TJ protein expression was assessed at this time point. Claudin-5 was significantly downregulated in ZIKV-U-infected animals and the BBB integrity was significantly disturbed in ZIKV-H-infected animals. Our results suggest that ZIKV penetrates the brain parenchyma early after infection with concurrent alterations of TJ protein expression and disruption of the BBB permeability in a strain-dependent manner.